The lssue of Suprašl Monastery Confessional Subordination and Character at the beginning of the 16th Century - Kirkienė, Genutė (Lietuvos istorijos studijos, 2006)
In historiography, Suprasi Monastery (the administrative district of Grodno, currently Poland near Bialystok) is almost universally treated as the center of Orthodoxy of the GDL of the 16th century, and its founder Aleksandras Chodkevičius (Pol. Aleksandr Chodkiewicz) is unquestionably regarded as an Orthodox. However, in modern historiography (J. Maroszek) the foundation of Suprasi Monastery is considered within the context of the realization of the programme of the Church Union at the turn of the 15th/16th c. The hypothesis has been put forward (R. Černius) that apart from the project of the Church Union of Jonas Sapiega, the nobleman of the GDL (common house of prayers devoted to the rites of two confessions - Catholic and Orthodox), there was another project of the implementation of the Church Union of the GDL Metropolitan Juozapas Bulgarinovičius. It is the Church founded by Jonas Sapiega in Ikazn (the administrative district of Braclav, current Belarus) that fully corresponds to the model of the common house of prayer. It becomes obvious that such house of prayer, together with the community of Orthodox believers, is subordinate to the Catholic Bishop, rather than to the Orthodox Metropolitan, so the Orthodox believers as if lose their separate church and autonomy, which was left to them by the Union of Florence. Meanwhile, Metropolitan Bulgarinovičius sought to strictly adhere to the agreements of the Union of Florence—he proposed the model of the universal Church Union, where the primate of the Pope is recognized, however, a separate Orthodox Church of the Greek rites remains.The fact of the foundation of Suprasi Monastery, which took place during the movement of the implementation of the programme of the Church Union, clearly showed the confessional orientation and direct relationship of Aleksandras Chodkevičius with Kiev Metropolitan Bulgarinovičius' programme of the renewal of the Church Union of Florence. All that determined Aleksandras Chodkevičius' decision to establish a monastery in his dominion, which remained „Orthodox" in a sense that it maintained formal relations with the metropolitan, though it gained considerable, legally substantiated autonomy. From the viewpoint of the Orthodox Church, this autonomy could mean that Suprasi was „open" to the Catholic Church, especially to the continuation of the informal local Church Union. In this case, the real confessional content of Suprasi is nothing but Catholicism of the Greek rites.
Keywords: -